ä¸¹æˆŽå¸ƒæ‹‰å›½ç«‹å¤§å¦å¸ˆèŒƒå¦é™¢æ±‰è¯ä¸“ä¸š2014å±Šå¦ç”Ÿ ä½¿ç”¨é‡è¯â€œåŒâ€ã€â€œå¯¹â€ã€â€œå‰¯â€çš„åè¯¯åˆ†æž - Winata, Adriana Mega (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractÂ This research analyzed the studentsgeneration 2014 in used the Numbers "shuang, dui, fu". The Objects of this research were students of Mandarin Language Study grade 2014 Tanjungpura University, with the number of 24 students, 3 students that male and 21 female students. The research method used is a test question. Based on the analysis data, found: When the students used the auxiliary word "shuang, dui, fu" a number of errors, the percentage of omission 35.17%; Percentage Addition 34,53; Percentage of misformation 52.29%; Percentage of Misordering 31.67%. The caused of misuse was the influence of the mother tongue. When the Student used the word "shuang, dui, fu" a number of errors occured, the percentage of error word "shuang" number 41,91%; error rate of "dui" 62.08%; Error percentage of "fu" word 56.55%. Â Keywords: Auxiliary Word Number "Shuang, dui, fu" ï¼ŒCategory of eror ï¼ŒThe Reason of eror Â